A cosmological reconstruction of the Higgs vacuum expectation value - Soumya Chakrabarti; V. Anagha; Selva Ganesh; Vivek Menon (European Physical Journal C: Particles and Fields)
Abstract We present a simple toy model of cosmic acceleration driven purely by a self-interacting scalar field embedded in theory of grand unification. The scalar self-interaction is Higgs-like and provokes a spontaneous symmetry breaking. The coefficient of the quadratic term in the self-interaction potential has an evolution and it leads to a cosmic variation of proton-to-electron mass ratio, $$μ $$ μ . We perform a cosmological reconstruction from the kinematic parameter jerk and discuss a few cosmological consequences of the theory. We also compare the theoretically calculated $$μ $$ μ variation with the observations of molecular absorption spectra from Cesium Atomic Clock data.